A community survey of asthmatic characteristics. Issue 6 (December 1975) - Burr, M L; St Leger, A S; Bevan, C; Merrett, T G
Abstract : A survey was undertaken among adults aged 20-44 years in a South Wales town. Persons with a history of wheezing with breathlessness and in the absence of a cold were identified by postal questionnaires and seen at a clinic, together with a sample of subjects without these symptoms. The response rates for the first and second stages of the survey were 99.6% and 91.0% respectively, and 574 subjects were ultimately seen. Asthmatic patients (those receiving treatment within the previous year) had some airways obstruction at rest, which increased after exercise. They also had strong allergic tendencies, as shown by personal and family history, skin tests, and serum IgE levels. The ex-asthmatics (those not receiving treatment within the previous year) showed these tendencies to a lesser extent. A larger group gave a history of wheezing but stated that they had never had asthma; in their response to exercise and allergic traits they resembled the control group rather than the asthmatics, and appeared to have the features of chronic bronchitis. Asthma and chronic bronchitis would therefore seem to be distinct entities within the population studied.